2014
DOI: 10.1111/1469-0691.12577
|View full text |Cite
|
Sign up to set email alerts
|

In vivo multiclonal transfer of blaKPC-3 from Klebsiella pneumoniae to Escherichia coli in surgery patients

Abstract: During active surveillance at the Mediterranean Institute for Transplantation and Advanced Specialized Therapies (ISMETT, Palermo, Italy) with the CARBA screening medium, five pairs of Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae and Escherichia coli strains were isolated in each of five colonized patients. In each patient, lateral gene transfer was demonstrated by comparing K. pneumoniae and E. coli strains, both possessing KPC-3, Tn4401a and pKpQIL-IT elements. The isolates were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 14 publications
1
27
1
Order By: Relevance
“…Among all of our strains with a bla KPC carbapenemase gene (581 strains), bla KPC-2 was the dominant allele (572 strains, 98.4%), including 293 CG258 strains (96.4%) and 197 CG307 strains (93.4%). Our results differ from those of other studies reporting that both bla KPC-2 and bla KPC-3 are found in CG258 K. pneumoniae (10, 13, 17, 20, 45, 53) and that CG307 was strongly associated with bla KPC-3 (39). CG307 strains expressing bla KPC-2 have been recently reported in Korea and Colombia (3436).…”
Section: Resultscontrasting
confidence: 99%
“…Among all of our strains with a bla KPC carbapenemase gene (581 strains), bla KPC-2 was the dominant allele (572 strains, 98.4%), including 293 CG258 strains (96.4%) and 197 CG307 strains (93.4%). Our results differ from those of other studies reporting that both bla KPC-2 and bla KPC-3 are found in CG258 K. pneumoniae (10, 13, 17, 20, 45, 53) and that CG307 was strongly associated with bla KPC-3 (39). CG307 strains expressing bla KPC-2 have been recently reported in Korea and Colombia (3436).…”
Section: Resultscontrasting
confidence: 99%
“…It is possible that a carbapenem-susceptible strain acquired a KPC plasmid from another strain (e.g., CG258) or that an ST307 strain was imported from somewhere else. Interestingly, this clone has been reported to harbor KPC-2 and KPC-3 in the United States (56) and in Italy (57), where it seems to be replacing ST258 (58,59). In addition, it has been reported to carry OXA-48 and CTX-M-15 in Morocco (60), which coincides with our results showing that 94.1% of ST307 isolates carried this ESBL.…”
Section: Discussionsupporting
confidence: 90%
“…This finding, along with the report by Gona et al [3] of a multiclonal cluster of cases of colonization and infection by KPC-producing K. pneumoniae (KPC-Kp) at the Mediterranean Institute for Transplantation and Advanced Specialized Therapies (ISMETT) in Palermo, Italy, prompted us to look for a possible spread of KPC-Kp isolates other than ST258 in the healthcare facilities of this city.…”
mentioning
confidence: 83%